Book Reviews (Journal of Finance, 1989)
Security Markets: Stochastic Models . By DARRELL DUFFIE. San Diego: Academic Press, 1988. Pp. xx + 358. Options: Theory, Strategy, and Applications . By PETER RITCHKEN. Glenview, IL: Scott, Foresman and Company, 1987. Pp. xiii + 414. Option Valuation . By STUART M. TURNBULL. Toronto: Holt, Rinehart and Winston of Canada, 1987, Pp. xv + 183.